The Political and Military Strategy of Salahuddin Al-Ayyubi in the Crusades: A Historical Analysis - Maghfiroh, Aghist Aulady; Firmansyah , Ahmad Ilham; Albab, Muhammad Ulil; Fahmi, Achmad (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to examine the political and military strategies of Salahuddin al-Ayyubi during the Crusades. The primary focus is to understand Salahuddin’s role in formulating political and military strategies, particularly during the Third Crusade (1187–1192), also known as the "Crusade of Kings." Using the library research method—analyzing books, articles, journals, and relevant historical documents—this study finds that Salahuddin al-Ayyubi was a wise Muslim leader and a brilliant military commander who played a pivotal role in the Crusades. His political strategies included uniting Muslims across Egypt, Syria, and Iraq to confront the Crusader forces, as well as using diplomacy to form alliances with other Muslim rulers and consolidate his power base. Meanwhile, his military strategies involved guerrilla tactics to disrupt the Crusader forces, cutting off supply lines, and deploying light cavalry and archers to weaken the enemy from a distance before launching major offensives.